Analysis of Outpatient Satisfaction with Health Services at Nusa Waluya II Floating Hospital (RSA) in Bau-Bau City, Buton Island, Southeast Sulawesi - Fini Fajrini; Ernyasih Ernyasih; Dadang Herdiansyah; Hardiman SG; Meita Veruswati; Tri Wulandari (Muhammadiyah Medical Journal, 2025)
Background: Patient satisfaction is an indicator of healthcare service quality, particularly in unique facilities such as the Floating Hospital (RSA) Nusa Waluya II, which serves remote areas. Purposes: This study aims to analyze factors influencing outpatient satisfaction at RSA. Methods: This analytical observational study with a cross-sectional design involved 50 patients selected through consecutive sampling. Data were collected using a SERVQUAL-based questionnaire and analyzed using the Chi-square test and logistic regression with a significance level of α=0.05. Results: 74% of patients were satisfied with the services, while 26% expressed dissatisfaction. Bivariate analysis showed that age <50 years was significantly associated with dissatisfaction (OR=2.83; 95% CI=1.15-6.97; P-value=0.021). Variables such as low income (OR=2.64; P-value=0.080), education (OR=1.53; P-value=0.348), and insurance ownership (OR=2.01; P-value=0.182) were not statistically significant, although trends were observed. Conclusion: Younger age (<50 years) is the primary risk factor for patient dissatisfaction at RSA Nusa Waluya II. These findings highlight the need for service quality improvements focused on the productive age group, as well as further research with a larger sample to confirm the role of economic and insurance factors.